Blending of palm mid-fraction, refined bleached deodorized palm kernel oil or palm stearin for cocoa butter alternative - Biswas, N.; Cheow, Y. L.; Tan, C. P.; Siow, L. F. (Springer-Verlag, 2016)
This study evaluated the physicochemical properties of palm mid-fraction (PMF), refined bleached deodorized palm kernel oil (RBDPKO) and refined bleached deodorized palm stearin (RBDPS) as binary mixtures in terms of their fatty acid compositions (GC), triacylglycerols (HPLC), solid fat contents (p-NMR), melting behaviors (DSC) and polymorphisms (XRD) for cocoa butter (CB) alternative formulations. All the PMF/RBDPKO and RBDPS/RBDPKO blends showed mixtures of short/long-chain fatty acids with corresponding triacylglycerols. 10–70 % PMF in RBDPKO showed a eutectic effect between 20 and 30 °C. However, a monotectic effect was observed at 10–15 °C for 20–40 % PMF in RBDPKO and 40–80 % of RBDPS in RBDPKO. For PMF/RBDPS blends, a monotectic effect was observed at less than 30 °C. Broad endotherms at 20–38 °C were observed for 30–50 % RBDPS in RBDPKO which are closer to CB, with polymorphs of β′1 > β′2 ≫ β2 based on XRD analysis. 50–80 % PMF in RBDPS exhibited significantly higher contents of long-chain fatty acids with the exception of stearic and lower constituents of monounsaturated triacylglycerols compared to CB. Broad endotherms were observed at 20–38 °C for 50–80 % PMF in RBDPS which are closer to CB, with β′1 ≫ β′2 > β2. Therefore, 20–40 % PMF in RBDPKO, 30–50 % RBDPS in RBDPKO and 50–80 % PMF in RBDPS could be used as CB substitutes because of their comparable physicochemical behaviors.